Tax incentives in developing countries and international taxation : a study on the relationship between income tax incentives for inward foreign investment in developing countries and taxation of foreign income in capital-exporting countries /: a study on the relationship between income tax incentives for inward foreign investment in developing countries and taxation of foreign income in capital-exporting countries. (1991) - Unknown
No abstract available